If I Enjoy, I Continue: The Mediating Effects of Perceived Usefulness and Perceived Enjoyment in Continuance of Asynchronous Online English Learning - Fang Huang; Shuiyin Liu (Education Sciences, 2024)
Although possessing flexibility and accessibility, asynchronous online courses suffer from high attrition and cause unsatisfactory learning performance, leading to a pressing need to understand factors influencing learners’ continuance of learning intention. Based on the expectation confirmation model, this study investigated perceived enjoyment as an extended variable to unpack the mediating effects of perceived usefulness and perceived enjoyment on the relationship between confirmation and continuance intention. Quantitative data from 254 learners enrolled in asynchronous online English courses were obtained for data analysis. Results indicate that confirmation significantly and positively affects learners’ continuance intention to take the asynchronous online English courses. Perceived usefulness and perceived enjoyment significantly mediate the relationship between confirmation and continuance intention. The total indirect effect of confirmation on continuance intention through perceived enjoyment and perceived usefulness and the combination of perceived enjoyment and perceived usefulness was 55.52%. Additionally, interviews with five learners revealed that despite limited real-time interaction, they highly value asynchronous online courses given that they promote self-regulated learning, offer choice freedom, foster a sense of achievement, and reduce anxiety and embarrassment risks that trigger their learning enjoyment. This study provided deep insights into factors influencing EFL learners’ decisions in asynchronous learning. Instructors are suggested to improve the quality of courses, provide timely feedback, and design tasks to improve learners’ perceptions of enjoyment and usefulness to further improve learners’ confirmation of online courses and their continuance intention to engage in online synchronous learning.